The Illicit Use of Prescription Stimulants on College Campuses: A Theory-Guided Systematic Review. (December 2015) - Bavarian, Niloofar; Flay, Brian R.; Ketcham, Patricia L.; Smit, Ellen
The illicit use of prescription stimulants (IUPS) is a substance use behavior that remains prevalent on college campuses. As theory can guide research and practice, we provide a systematic review of the college-based IUPS epidemiological literature guided by one ecological framework, the theory of triadic influence (TTI). We aim to assess prevalence, elucidate the behavior's multietiological nature, and discuss prevention implications. Peer-reviewed studies were located through key phrase searches (prescription stimulant misuse and college, "prescription stimulant misuse" and "college, " illicit use of prescription stimulants in college, and nonmedical prescription stimulant use in college students) in electronic databases (PubMed, PubMed Central, and EBSCO Host) for the period 2000 to 2013. Studies meeting inclusion criteria had their references reviewed for additional eligible literature. Statistically significant correlates of IUPS in the 62 retrieved studies were organized using the three streams of influence and four levels of causation specified in the TTI. Results show that the prevalence of IUPS varies across campuses. Additionally, findings suggest the behavior is multifaceted, as correlates were observed within each stream of influence and level of causation specified by the TTI. We conclude that IUPS is prevalent in, but varies across, colleges and is influenced by intrapersonal and broader social and societal factors. We discuss implications for prevention and directions for future research.